The use of Value-at-Risk methodology in the assessment of investor’s risk attitudes on the precious metals market - Krężołek, Dominik (Zastosowanie metodologii Value-at-Risk w ocenie postaw inwestora wobec ryzyka na rynku metali, 2017)
The decision making process is directly associated with risk, no matter what area of interest it is. In the case of financial investments we can define a special type of risk called investment risk. Taking into account the financial time series of assets’ characteristics (prices, returns), small deviations of future values comparing to their expected level are not a major threat to the investor’s portfolio. In contrast, if the changes in prices/returns are significant, unpredictable and result from unexpected and adverse events, one should pay attention to the proper risk measurement. The topic of this article refers to the new family of risk measures related to investments in assets on the precious metals market. These risk measures are called the GlueVaR risk measures. The name itself suggests that the GlueVaR is related to the commonly used measure of risk – VaR. As will be presented in the article, the family of the GlueVaR risk measures may be expressed as a linear combination of VaR and conditional VaR for fixed tolerance levels. Moreover, the new risk measure allows for assessing risk more personally, taking into account the investor’s attitudes towards risk. If portfolio investments are of interest, the GlueVaR risk measures meet the assumption of subadditivity. This property of risk measure is required, as it is strongly related to the diver-sification problem
Ekonometria = Econometrics, 2017, Nr 3 (57), s. 101-112
Keywords: risk; precious metals market; subadditivity; VaR; GlueVaR; ryzyko; rynek metali szlachetnych; subaddytywność